2020
DOI: 10.3390/nu12082445
|View full text |Cite
|
Sign up to set email alerts
|

A High Polyphenol Diet Improves Psychological Well-Being: The Polyphenol Intervention Trial (PPhIT)

Abstract: Mental ill health is currently one of the leading causes of disease burden worldwide. A growing body of data has emerged supporting the role of diet, especially polyphenols, which have anxiolytic and antidepressant-like properties. The aim of the present study was to assess the effect of a high polyphenol diet (HPD) compared to a low polyphenol diet (LPD) on aspects of psychological well-being in the Polyphenol Intervention Trial (PPhIT). Ninety-nine mildly hypertensive participants aged 40–65 years were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 52 publications
(60 reference statements)
2
37
0
Order By: Relevance
“…During the lockdown, Italian residents were required to stay at home and only essential needs/services were permitted, with huge limitations in terms of working activities that were converted into home working as far as possible. As a consequence, daily routine was dramatically disrupted with potential negative effects on mental health and dietary habits: the latter are highly susceptible to psychological well-being [ 3 , 4 ] and vice versa [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the lockdown, Italian residents were required to stay at home and only essential needs/services were permitted, with huge limitations in terms of working activities that were converted into home working as far as possible. As a consequence, daily routine was dramatically disrupted with potential negative effects on mental health and dietary habits: the latter are highly susceptible to psychological well-being [ 3 , 4 ] and vice versa [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, psychological wellbeing is lower in those with cardiometabolic disease [ 61 ] and a high intake of dietary polyphenols has been shown to enhance indices of psychological wellbeing [ 62 ]. Therefore, general psychological wellbeing will be examined using the COOP WONCA questionnaire [ 63 ], depressive symptoms using the Beck Depression Inventory [ 64 ] and state/trait anxiety with the State Trait Anxiety Inventory [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, effective prevention and treatment strategies are required to overcome depression. Several studies have shown that the antidepressant effects of polyphenols, especially dietary polyphenols, have the potential to be widely used in depression worldwide because their antidepressant effects can be cost-effective [ 9 , 10 , 11 , 12 ]. Most dietary polyphenols are associated with reduced symptoms of depression, and consumption of some polyphenols significantly reduces depressive symptoms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%